Managing fashion creativity. The history of the Chambre Syndicale de la Couture Parisienne during the interwar period - Pouillard, Veroniqué (Investigaciones de Historia Económica, 2019)
In the creative industries, managing creativity and business is a complex process. This article explores the history of the oldest and most prestigious employers’ syndicate in the fashion industry, the Chambre Syndicale de la Couture parisienne (1868) during the interwar period, a time of crisis and change. The study of the private, unpublished archives of the syndicate allows us to understand the tensions between management and creativity. Paris fashion entrepreneurs federated to face external and internal challenges. Two major topics emerge from their concerns: the relations of entrepreneurs with the workforce, and the protection of intellectual property rights. The Chambre Syndicale’s members, in response, developed social services, schools for apprentices, lobbied the French institutions, and shared information among themselves. In so doing, the Chambre developed unmatched politics of exclusivity that underline the role of the syndicate as a gatekeeper.